Evolutionary perspectives, heterogeneity and ovarian cancer: a complicated tale from past to present - Patriciu Achimas-Cadariu; Paul Kubelac; Alexandru Irimie; Ioana Berindan-Neagoe; Frank Rühli (BMC, 2022)
Abstract Ovarian cancer is composed of a complex system of cells best described by features such as clonal evolution, spatial and temporal genetic heterogeneity, and development of drug resistance, thus making it the most lethal gynecologic cancer. Seminal work on cancer as an evolutionary process has a long history; however, recent cost-effective large-scale molecular profiling has started to provide novel insights coupled with the development of mathematical algorithms. In the current review, we have systematically searched for articles that focused on the clonal evolution of ovarian cancer to offer the whole landscape of research that has been done and highlight future research avenues given its characteristic features and connections to evolutionary biology.